Sympathetic skin response following single and combined sound and electrical stimuli in young healthy subjects - Wiertel-Krawczuk, Agnieszka; Hirschfeld, Adam S.; Huber, Juliusz; Wojtysiak, Magdalena; Szymankiewicz-Szukała, Agnieszka (Journal of Medical Science, 2016)
Introduction. Sympathetic skin response (SSR) is applied in evaluation of dysfunctions in autonomic nervous system. Among others, electrical and sound stimuli are most frequently used to evoke SSR.Aim. The aim of this study was to determine if the bell ring stimulus with parameters different from standard sound stimulation evokes similar reactions in autonomic system as electrical stimulus with defined parameters. Material and methods. SSR parameters were recorded following simultaneous sound and electrical stimulation. Twenty young volunteers (aged 23 ± 2.1 years) were examined once with SSR and R-R interval variation (RRIV) tests in order to confirm lack of functional changes in autonomic nervous system. Results. Values of mean amplitudes of SSR were always higher during recordings from upper limbs than the lower ones irrespective of the three types of applied stimuli. Mean values of latencies were comparable when SSR were induced with acoustic, electrical and both stimuli during recordings performed from upper and lower extremities. Bell ring stimulus influenced only mean values of SSR area recorded both from upper (p ? 0.011) and lower (p ? 0.023) extremities. Heart beats variability in RRIV recordings changed at 13.5% which is comparable to results obtained by other authors. Conclusions. Results indicate that the application of different modalities stimuli evokes SSR with comparable parameters. Each of them can be used for objective evaluation of the sympathetic nervous system function. Both SSR and RRIV tests evaluating the function of two effector types should be applied for the diagnosis of the probable dysautonomia in patients who show unclear clinical symptoms.
Keywords: sympathetic skin response; acoustic stimulus; electrical stimulus; R-R interval variation; normative values; autonomic system